High-Performance Lithium-Sulfur Batteries With an IPA/AC Modified Separator - Guo, Yafang; Jiang, Aihua; Tao, Zengren; Yang, Zhiyun; Zeng, Yaping; Xiao, Jianrong (Frontiers in Chemistry, 2018)
To inhibit the polysulfide-diffusion in lithium sulfur (Li-S) batteries and improve the electrochemical properties, the commercial polypropylene (PP) was decorated by an active carbon (AC) coating with lots of electronegative oxygenic functional group of –OH. Owing to the strong adsorption of AC and the electrostatic repulsion between the –OH and negatively charged polysulfide ions, the Li-S batteries demonstrated a high initial discharge capacity of 1656 mAh g-1 (approximately 99% utilization of sulfur) and the capacity can still remain at 830 mAh g-1 after 100 cycles at 0.2 C. Moreover, when the rate was increased to 1 C, the batteries could also possess a discharge capacity of 1143 mAh g-1. The encouraging cycling stability make clear that this facile approach can successfully restrain the shuttle effect of polysulfides and make further progress to the practical application of Li-S batteries.